High purity hematite (Fe2O3) from beach sands for soft ferrite magnetic materials application. Issue 1 (November 2021) - Rahwanto, A; Machmud, M N; Fauzi; Irhamni, I; Zulfalina, Z; Jalil, Z
Abstract: Actually, the potential and deposites are rich and spread in many place, but the process from raw material to industrial product is not optimal yet. In this work, the manufacture of iron sand was done using direct reduction technique by compact coals as reductor. The carbon compound of coals were using for releasing oxide in magnetite compounds (Fe3 O4 ) of iron sand, so it could be transformed to Fe phase. The iron sand was firstly milled using high energy ball mill (HEBM) for 0, 10, 20, and 40 hours. Then the iron sands samples were mixed with coals, bentonite and compacted using hydraulic press. Then, loaded into furnace and sintered at 700 °C, 800 °C, and 900 °C. As the results, it was identified (using XRF) that the major phase was Fe2 O3 (75.40 %). Consistent with XRF results, the phase composition observation by using XRD was shown that the major phase of sample was Fe2 O3 (hematite). It was also shown that the crystallite size of the sample was around 8 nm, as calcultaed using Scherrer formula. The magnetic behavior investigation was showed that the decreasing in magnetic saturation value (Ms) and remanent (Br) and followed by increasing the coercivity value (Hc).